A comparative study of intraocular pressure changes in postmenopausal normotensive and hypertensive women - N, Nirmala; A, Adhilakshmi; Jain, Harshila; U, Karthika Priyadarshini (International Journal of Research in Medical Sciences, 2017)
Background: Elevated intraocular pressure is a major modifiable risk factor for preventing glaucoma. Changes in intraocular pressure are directly and significantly associated with changes in blood pressure. Menopausal women with hypertension are at an increased risk of developing elevated intraocular pressure. Aim of current study was to compare the intraocular pressure changes in postmenopausal normotensive and hypertensive women. Methods: 35 normotensive and 35 hypertensive (based on JNC7 classification) postmenopausal women in the age group of 45-55 years participated in the study. Blood pressure was recorded in the sitting position with a mercury sphygmomanometer. Intraocular pressure was measured using Goldmann applanation tonometer. Results: Mean Intraocular Pressure in postmenopausal normotensive women was 13.01 ± 2.61 mmHg while that of postmenopausal hypertensive women was 15.15 ± 2.16 mmHg which was statistically significant. A statistically significant correlation was observed between IOP and systolic blood pressure and positive correlation was obtained between IOP and diastolic blood pressure in postmenopausal hypertensive women. Conclusion: Menopausal women are at an increased risk of developing hypertension due to age, hormonal changes and obesity which may lead to increased IOP. IOP is also directly and significantly related to systemic blood pressure hence postmenopausal women with systemic hypertension need periodic ophthalmologic examination. Detecting early IOP changes will help them in identifying the risk groups and formulating strategies for screening glaucoma.